PENGEMBANGAN PERMAINAN TRADISIONAL KELERENG UNTUK MENINGKATKAN KERJASAMA SISWA - Tri Septiana Dewi; Tri Pelita; Shintia; Hamdi Akhsan (STKIP Subang, 2024)
The development of the times is getting faster, technology is also experiencing a very advanced growth. This affects the way or process of playing children. Nowadays, children are more familiar with modern games or better known as using digital, technology, and the internet. There are many modern games that are favoured by children, both offline and offline based. Offline games such as playstation (PS), while online games such as FreeFire, Mobile Legend, Video games, and many more. So that children know less about traditional games. Whereas traditional games are better for children's social development. With traditional games, children have more sense of cooperation, togetherness, socialisation, and mingle with their friends because they meet directly. The purpose of this study was to examine the development of traditional marbles games in improving the cooperation skills of elementary school students. This type of research is qualitative which describes how the development of the traditional game of marbles from time to time and how its role on the cooperation skills of students. This type of research is qualitative which describes how the development of the traditional game of marbles from time to time and how its role on students' cooperation skills. The results showed that students have shown social skills in terms of co-operation, adjusting, interacting, self-control, empathising, obeying rules, and respecting others. This is a series of social skills that students need to have in relation to their role as social beings. The social skills possessed by children have reached the success target expected by researchers, as stated in the success indicators. The development of children's social skills that occurs is a process of children's self-adjustment to the surrounding environment both with friends and teachers. In addition, children also adjust to new rules and experiences in order to do well and be accepted by their playmates and others.